(untitled) (International Journal of Engineering and Computer Science, 2017)
In this paper tuning of PID Controller for higher order system is given. Conventionally higher order system is reduced to lower order model, and then controller is designed. But in this method higher order system is considered as it is and controller designed based on desired Phase Margin (PM) method. Analytical expression for controller design is given which is based Mikhalevich method. The Mikhalevich method gives a way to select the desired phase margin.